CONSTITUTIONALISM AND RULE OF LAW IN ECONOMIC GOVERNANCE (Journal of actual problems of jurisprudence, 2024)
This abstract presents an analysis of the pivotal role played by constitutionalism and the Rule of Law in economic governance, emphasizing their significance, challenges, and strategies for fortification. Constitutionalism and the Rule of Law stand as foundational pillars, ensuring stability, fairness, and conducive environments for economic activities. This study reviews the threats to these principles, including political interference, weak institutions, and regulatory capture, which undermine their effectiveness. Proposed strategies for strengthening these principles encompass institutional reforms, civic engagement, judicial enhancements, and ethical leadership promotion. The outlook emphasizes the criticality of upholding these principles for sustainable economic development, reduced disparities, and equitable resource allocation. The conclusion advocates for sustained efforts to fortify constitutionalism and the Rule of Law to build resilient and inclusive economic systems, fostering societal progress and global stability.In general, the essence of the topic of constitutional economics lies in the development of rational rules for the interaction between the government and the business community and is expressed in the concretization and protection of the principles of the foundations of the constitutional system, ensuring the stability of existing economic conditions and legal security. To a greater extent, the system of constitutional economy can be traced through determining the content of the function of the state in the field under study.Key words: constitutionalism, the rule of law, Economic Management, Sustainable Development, Challenges, Strategies, institutional reforms.